Model Program Pemberdayaan Masyarakat Desa Berbasis Komunitas - Yusuf Adam Hilman; Elok Putri Nimasari (Universitas Muhammadiyah Ponorogo, 2018)
This study examines the issue of community empowerment, which is considered to be a solution problem of poverty, which is more interesting when the community of